2019
DOI: 10.3390/nu11020342
|View full text |Cite
|
Sign up to set email alerts
|

What Can Dietary Patterns Tell Us about the Nutrition Transition and Environmental Sustainability of Diets in Uganda?

Abstract: Uganda is undergoing dietary transition, with possible environmental sustainability and health implications, particularly for women. To explore evidence for dietary transitions and identify how environmentally sustainable women’s dietary patterns are, principal component analysis was performed on dietary data collected using a 24 h recall during the Uganda Food Consumption Survey (n = 957). Four dietary patterns explained 23.6% of the variance. The “traditional, high-fat, medium environmental impact” pattern w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 35 publications
12
30
0
Order By: Relevance
“…For each food group under the four classifications, the amount of intake (in grams) was obtained by summing up the intake amount of all food items identified under that food group. Intake quantity (in grams) per food group was then standardized—mean = 0 and standard deviation = 1—to account for large variances that may exist across the food groups [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For each food group under the four classifications, the amount of intake (in grams) was obtained by summing up the intake amount of all food items identified under that food group. Intake quantity (in grams) per food group was then standardized—mean = 0 and standard deviation = 1—to account for large variances that may exist across the food groups [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…The standardized values were fed into the PCA tool as primary data to extract patterns. Varimax with Kaiser Normalization was used as a rotation method to extract patterns that are not correlated to each other, but rather correlations between food groups that describe patterns [ 16 , 17 , 18 ]. After comparison, the 11-food grouping was chosen for Tanzania, Uganda, and East Africa, while the 12-food grouping was selected for Kenya.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…If the waste of plant foods is considerably greater than animal products, the impact may be greater. Thus, the impacts and changes necessary to reduce the impact generated by FW should be evaluated, considering all variables [ 57 , 58 ].…”
Section: The Food Waste Generation and Impactsmentioning
confidence: 99%
“…In a study carried out in Uganda which assessed women's dietary patterns and their relationship to sustainability by assessing the environmental and economic impact caused by food production found that high intake of meat, chicken, and soup was the dietary profile with greater impact. The consumption of legumes, roots, tubers, vegetables, and fresh fruits was considered the dietary pattern with the least environmental and economic impact [59]. It is important to highlight that multiple factors influence fruit and vegetable ingestion, including economic barriers, inadequate nutrition knowledge and awareness, food preferences and attitudes, and cultural factors.…”
Section: Main Types Of Activities Performed In Food Servicesmentioning
confidence: 99%